2015
DOI: 10.1021/acs.jpcc.5b00105
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Fe Electrolyte Impurities on Ni(OH)2/NiOOH Structure and Oxygen Evolution Activity

Abstract: Ni-(oxy)hydroxide-based materials are promising earthabundant catalysts for electrochemical water oxidation in basic media. Recent findings demonstrate that incorporation of trace Fe impurities from commonly used KOH electrolytes significantly improves oxygen evolution reaction (OER) activity over NiOOH electrocatalysts. Because nearly all previous studies detailing structural differences between α-Ni(OH) 2 /γ-NiOOH and β-Ni(OH) 2 /β-NiOOH were completed in unpurified electrolytes, it is unclear whether these … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

111
994
10
9

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 939 publications
(1,124 citation statements)
references
References 52 publications
111
994
10
9
Order By: Relevance
“…30 What is different between the observations here and in ref. 29, and the report by Trześniewski et al is that the "active oxygen" species was observed along with the oxidation of Ni 2+ to Ni 3+ , as indicated by UV-vis and XAS data, whereas the additional oxide species in our study and, likewise, the Raman peak at 560 cm -1 in ref. 29, arise before the onset of Ni oxidation.…”
Section: Operation Of the Thin Film Electrochemical Cellsupporting
confidence: 88%
See 1 more Smart Citation
“…30 What is different between the observations here and in ref. 29, and the report by Trześniewski et al is that the "active oxygen" species was observed along with the oxidation of Ni 2+ to Ni 3+ , as indicated by UV-vis and XAS data, whereas the additional oxide species in our study and, likewise, the Raman peak at 560 cm -1 in ref. 29, arise before the onset of Ni oxidation.…”
Section: Operation Of the Thin Film Electrochemical Cellsupporting
confidence: 88%
“…This is consistent with recent in situ Raman measurements within the same potential region, which revealed a spectral signature of NiOOH prior to the oxidation wave in the corresponding voltammogram. 29 Recently, Trześniewski et al…”
Section: Operation Of the Thin Film Electrochemical Cellmentioning
confidence: 99%
“…Polarization curves were recorded after certain durations of set-point operation as shown in Figure 6b. Due to electrode activation, perhaps from iron impurities as discussed above, 53 the onset potential was observed to improve as experiments ran for longer periods of time and more polarization sweeps were recorded. Currently, Fe-doped nickel hydroxides are even considered the most active alkaline oxygen evolution catalyst.…”
Section: Resultsmentioning
confidence: 99%
“…Iron is present as impurities in the electrolyte, but is also bleeding from external system components exposing steel to the heated electrolyte such as pumps and valves. It is well known that iron impurities significantly improve the oxygen evolution activity of nickel, 52,53 but other factors such as membrane uniformity, precision of electrode alignment, and contamination are expected to affect the appearance of the polarization curves as well.…”
Section: Resultsmentioning
confidence: 99%
“…The behavior of Fe-doped Ni (Fe:Ni) oxide films under basic conditions (1 M KOH) has been revisited (9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19) and in this recent body of work, the role of Fe in these films has come under debate. X-ray absorption spectra of Fe:Ni oxide films supported by computational studies have led to the contention that Fe 3+ species are the active sites for water oxidation (13).…”
mentioning
confidence: 99%